2016
DOI: 10.1038/srep39059
|View full text |Cite
|
Sign up to set email alerts
|

Slit-Robo GTPase-Activating Protein 2 as a metastasis suppressor in osteosarcoma

Abstract: Osteosarcoma is the most common primary bone tumor, with metastatic disease responsible for most treatment failure and patient death. A forward genetic screen utilizing Sleeping Beauty mutagenesis in mice previously identified potential genetic drivers of osteosarcoma metastasis, including Slit-Robo GTPase-Activating Protein 2 (Srgap2). This study evaluates the potential role of SRGAP2 in metastases-associated properties of osteosarcoma cell lines through Srgap2 knockout via the CRISPR/Cas9 nuclease system and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 29 publications
4
24
0
Order By: Relevance
“…srGAP3 expression is decreased in the majority of breast cancer cell lines, and loss of srGAP3 leads to both anchorage-independent growth and increased cell invasion and/or migration; these changes are GAP dependent, suggesting that srGAP3 acts as a tumor suppressor through its ability to inactivate Rac (Lahoz and Hall, 2013). Similar phenotypes are observed upon srGAP2 loss in osteosarcomas (Marko et al, 2016). Separating correlation from causation in the numerous clinical studies that have been reported will be challenging, but these studies clearly implicate srGAPs in a wide range of human disease.…”
Section: Box 2 Srgaps In Non-neuronal Diseasementioning
confidence: 78%
“…srGAP3 expression is decreased in the majority of breast cancer cell lines, and loss of srGAP3 leads to both anchorage-independent growth and increased cell invasion and/or migration; these changes are GAP dependent, suggesting that srGAP3 acts as a tumor suppressor through its ability to inactivate Rac (Lahoz and Hall, 2013). Similar phenotypes are observed upon srGAP2 loss in osteosarcomas (Marko et al, 2016). Separating correlation from causation in the numerous clinical studies that have been reported will be challenging, but these studies clearly implicate srGAPs in a wide range of human disease.…”
Section: Box 2 Srgaps In Non-neuronal Diseasementioning
confidence: 78%
“…Notably, while down-regulation of SrGAP2 contributes to a more aggressive phenotype, most likely by enhancing cell migration, down-regulation of srGAP3 promotes Rac1-dependent, anchorage-independent cell growth (49,50). …”
Section: Emerging Paradigms In Rho Gtpase Hyperactivation In Cancermentioning
confidence: 99%
“…Stable shRNA knockdown lines were established via puromycin selection at 1 μg/mL. Overexpression vectors were generated using the human SEMA4C cDNA sequence (#40035253, Dharmacon) and vectors/cell lines were established using previously described methodology [20, 21].…”
Section: Methodsmentioning
confidence: 99%
“…Wound healing assays were performed as previously described [20]. Briefly, 1 × 10 4 cells were plated into a removable 2-well silicone culture insert which generated a defined cell-free gap (ibidi).…”
Section: Methodsmentioning
confidence: 99%